STRUKTUR DAN KERAGAMAN KOMUNITAS KEPITING DI KAWASAN HUTAN MANGROVE STASIUN KELAUTAN UNIVERSITAS RIAU, DESA PURNAMA DUMAI - Rasoel Hamidy (Program Pascasarjana Universitas Riau, 2010)
This study was carried out from October to December 2008. The species collected consisted of10 species of crabs representing 4 family and 4 genus. The result of this study showed thatdiversity of crab and productivity of mangrove area at position is enough for animal life, andless ecology pressure.